Pembangunan Website Manajemen Persuratan Pada Balai Pemasyarakatan Klas 1 Malang Menggunakan Metode Prototyping - Prita Nur Rizky Faridiani; Adam Hendra Brata; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Balai Pemasyarakatan Klas 1 Malang is a law institute which doing correspondence activity on it's daily basis, such as submission of letters, letters' archiving, and letters' numbering. When doing this routine, there's some lack of time efficiency. Moreover, there's no monitoring on the routine, resulting Kabapas not being able to monitor on his employee's activity. Hence, it needs a system that can make the administrative process shorter so it will be more efficient and monitoring of status on the documents worked on. The system also can manage letter's numbering to avoid overlapping. A development of correspondency management based on website is carried out to overcome the problems that arise. This system developed with prototyping development method. During the study, there are obtained 4 actors who can interact with the system, a total 58 functional requirements, and 1 non-functional requirements. This system will be tested using unit testing, validation testing, and compatibility testing.